If it's not what You are looking for type in the equation solver your own equation and let us solve it.
18z-1=-12+29z
We move all terms to the left:
18z-1-(-12+29z)=0
We add all the numbers together, and all the variables
18z-(29z-12)-1=0
We get rid of parentheses
18z-29z+12-1=0
We add all the numbers together, and all the variables
-11z+11=0
We move all terms containing z to the left, all other terms to the right
-11z=-11
z=-11/-11
z=1
| 10k+18=16k-30 | | 4(5x+6)=20x+6 | | (1+2.5x)(0.5-x)=0.5 | | 30p-55=19p-99 | | 12+14x=20x-60 | | 10n^2+2=192 | | 18(1+a/2)=18(3a+4/9 | | 18(1+a/2=18(3a+4/9 | | j-3=1/6 | | 0.5=0.82^x | | 12=3(k+4) | | m+20=42 | | 3x–1=5x-6 | | -3=25b/32 | | X*y=67/4(5) | | 1/9^x=729 | | 49x^2-28x+4=12 | | 2x+7x=2170 | | 10x(10)+17=180 | | 5z+8=10 | | 13x+2x+22=-23 | | T={(6+7)x4}+2(1/2(6)(4) | | 6s–11=6s+24 | | 4x/5+6=15 | | 3×(2a+6)=3a-12 | | 3v=7v-96 | | 7x+54=12x-40 | | 8j+2-3j=+8-5j | | 64=-16t^2+96t+112 | | 3x²-15=33 | | -4.9x^2-4.5x+14=0 | | 9x-8=7x–4 |